2021
DOI: 10.1021/acsami.1c07987
|View full text |Cite
|
Sign up to set email alerts
|

B,N-Doped PdRu Aerogels as High-Performance Peroxidase Mimics for Sensitive Detection of Glucose

Abstract: Among plentiful porous nanomaterials, noble metal aerogels taken as nanozymes attract broad attention in sensing applications with their distinct enzyme mimic functions. In the catalytic field, the heteroatom doping strategy is a kind of way with great promise in improving the enzyme mimic activity of noble metal aerogels. In this experiment, we find a type of creative materials that were prepared by the fast and simple method. Due to the unique porous structure and synergetic effect from doped atoms, PdRu aer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 59 publications
(60 reference statements)
0
19
0
Order By: Relevance
“…Typically, peroxidase‐mimic nanozymes can induce the catalytic decomposition of H 2 O 2 to generate the hydroxyl radicals (•OH), which then oxidize colorless TMB to blue oxTMB. [ 60–62 ] To confirm whether this mechanism also applies to our Au hydrogels, the terephthalic acid (pTA) was used as a fluorescent probe for determining •OH, which can form highly fluorescent 2‐hydroxyterephthalic acid with a characteristic emission at around 430 nm upon reacting with •OH. [ 63 ] Indeed, upon adding pTA to the Au hydrogels and H 2 O 2 system, it can be clearly seen that the fluorescence intensity at 438 nm increased significantly (Figure S22A, Supporting Information), confirming the generation of •OH during the catalytic reaction of Au hydrogels in the TMB‐H 2 O 2 system.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Typically, peroxidase‐mimic nanozymes can induce the catalytic decomposition of H 2 O 2 to generate the hydroxyl radicals (•OH), which then oxidize colorless TMB to blue oxTMB. [ 60–62 ] To confirm whether this mechanism also applies to our Au hydrogels, the terephthalic acid (pTA) was used as a fluorescent probe for determining •OH, which can form highly fluorescent 2‐hydroxyterephthalic acid with a characteristic emission at around 430 nm upon reacting with •OH. [ 63 ] Indeed, upon adding pTA to the Au hydrogels and H 2 O 2 system, it can be clearly seen that the fluorescence intensity at 438 nm increased significantly (Figure S22A, Supporting Information), confirming the generation of •OH during the catalytic reaction of Au hydrogels in the TMB‐H 2 O 2 system.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the catalytic activity of the present Au hydrogels ( v max ) is comparable and/or higher than those reported metal aerogels fabricated by other approaches. [ 44,59–61 ] Even compared with other reported nanozymes, [ 69–75 ] these Au aerogels exhibit a superior peroxidase‐like property, which can be attributed to their hierarchical porous structures and abundant catalytically active metal nodes within the 3D networks. In one recent study, Eychmüller et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the first study of Fe 3 O 4 nanomaterials for peroxidase-mimicking activity in 2007, a variety of inorganic materials including noble metals, metal oxides, and carbonbased materials have been reported. [12][13][14] Particularly, artificial enzymes consisting of redox-active metals are now much sought-after for their several distinctive features: (1) metal nanomaterials possess high interfacial stability to survive in harsh environments; (2) their preparation is easily controlled to produce a large number of nanomaterials with high quality; and (3) their surface is easily modified by ligands and biomolecules, enabling a broader application. 15,16 The main challenge for the practical applications of metalbased peroxidase mimics has been the incremental improvement of their catalytic efficiency, a crucial parameter for their performance.…”
Section: Introductionmentioning
confidence: 99%
“…2,19 Heteroatom doping offers an effective way to increase electrocatalytic activity, [20][21][22][23][24] which can tailor the metal-H binding energy and electron orbital structure, thus optimizing the free energy of hydrogen species on the catalyst surface. [25][26][27] Among them, nitrogen atoms with small atomic radii can easily bind into the gaps of metal atoms and thus enhance catalytic performance. 28 In addition, mesoporous nanomaterials can offer rich active sites to promote catalytic activity.…”
mentioning
confidence: 99%